Urban health: Needs urgent attention - Satish Kumar; Sanjiv Kumar; Basab Gupta (Wolters Kluwer Medknow Publications, 2018)
Urban population in our country has increased at an annual rate of 2.7% during the last decade and it is estimated that by 2031, there would be about 600 million people living in urban India. The fast pace of urbanization has come to stay with increasing proportion of urban poor and vulnerable with health indicators much worse than their rural counterparts. The need to provide health care to urban poor has been emphasized in the past in various health committees' reports and National 5-year Development Plans, but no significant dent was made to improve the urban health scenario of the country. The National Urban Health Mission launched in May 2013 provides us a concrete mechanism to address special health needs of urban population with focus on urban poor. There is a strong need to set up primary healthcare system in urban areas and systematically deal with urban health challenges in terms of vector-borne diseases, rising incidence of noncommunicable diseases, air pollution and acute respiratory infections, road traffic accidents, trauma, and injuries. The initiatives to address these challenges do not remain confined to health sector alone but also need to be supported by sectors other than health such as social welfare, women and child development, road transport and highways, school education, drinking water, and sanitation. We really need to address wider and social determinants of health to effectively improve the urban health scenario.